2021
DOI: 10.3390/nu14010123
|View full text |Cite
|
Sign up to set email alerts
|

Coix Seed Diet Ameliorates Immune Function Disorders in Experimental Colitis Mice

Abstract: Coix seed is a functional food in the Chinese diet that possesses the ability to alleviate ulcerative colitis clinically. However, the underlying mechanisms remain ambiguous. In this study, we investigated the protective effect of the Coix seed diet on experimental colitis mice. The mice were randomly divided into four groups: control group, model group, Coix seed feed group, and positive control group. The maintenance feed of the mice was replaced with Coix seed feed 10 days before orally administering the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…CSE has a protective effect on intestinal mucosal immunity, helps to repair the intestinal barrier, and promotes the transmission of hypoglycemic signaling pathways. In a study on the protective effect of CSE on colitis mucosa, T cell regulation was one of the targets of CSE ( 47 , 48 ), reducing the oxidative stress level in the intestine, reducing the secretion of TNF-α in the intestinal mucosa, and protecting the intestinal mucosa ( 47 , 49 ). Research on blood sugar regulation of type 2 diabetes by CSE found that CSE can reduce colonic mucosal damage, increase serum insulin levels and increase HLDL levels to control blood sugar.…”
Section: Discussionmentioning
confidence: 99%
“…CSE has a protective effect on intestinal mucosal immunity, helps to repair the intestinal barrier, and promotes the transmission of hypoglycemic signaling pathways. In a study on the protective effect of CSE on colitis mucosa, T cell regulation was one of the targets of CSE ( 47 , 48 ), reducing the oxidative stress level in the intestine, reducing the secretion of TNF-α in the intestinal mucosa, and protecting the intestinal mucosa ( 47 , 49 ). Research on blood sugar regulation of type 2 diabetes by CSE found that CSE can reduce colonic mucosal damage, increase serum insulin levels and increase HLDL levels to control blood sugar.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] The current results indicate that CHRNA7-Ca 2+ -PI3K-PIP3-AKT-(MTOR, NFk β , BIRC5) is a key target signaling pathway of the activity of active components in coix seed for treatment of CRC. Zhou et al [ 6 ] reported that injection of coix seed oil effectively reduced the pain level of cancer patients. Previous findings and the results of this study indicate that the analgesic mechanism of coix seed active compounds may be associated with targeting of the neuroactive ligand-receptor interaction the signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…of CRC. Zhou et al [6] reported that injection of coix seed oil effectively reduced the pain level of cancer patients. Previous findings and the results of this study indicate that the analgesic mechanism of coix seed active compounds may be associated with targeting of the neuroactive ligand-receptor interaction the signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials have confirmed that Coix seed has the effect of relieving ulcerative colitis. By acting on important targets such as T-cell regulation, the Coix seed feed can maintain the complete blood count at a normal level, relieve oxidative stress, reduce inflammatory cytokine secretion and pathological score, and finally relieve the symptoms of colitis ( Zhou et al, 2021b ). Gu et al (2020a ) combined network pharmacology technology with GEO gene chips and found that oral administration of Indigo naturalis (IN) could hinder the further development of ulcerative colitis, and the specific therapeutic effect may involve the activation of systemic immunity, mainly acting on the JAK-STAT and IL-17 signaling pathways.…”
Section: Application Of Network Pharmacology In the Treatment Of Ulce...mentioning
confidence: 99%